2011
DOI: 10.1159/000327253
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Traumatized Victims of War and Torture: A Randomized Controlled Comparison of Narrative Exposure Therapy and Stress Inoculation Training

Abstract: Background: The aim of the present randomized controlled trial was to compare the outcome of 2 active treatments for posttraumatic stress disorder (PTSD) as a consequence of war and torture: narrative exposure therapy (NET) and stress inoculation training (SIT). Methods: Twenty-eight PTSD patients who had experienced war and torture, most of them asylum seekers, received 10 treatment sessions of either NET or SIT at the Outpatient Clinic for Refugees, University of Konstanz, Germany. Posttests were carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 62 publications
0
101
2
5
Order By: Relevance
“…However, our mean dropout rate (25.2%) fell within the range of dropout rates in cognitive-behavioral therapy (e.g. 32% [19] and 15% [20,21]). …”
Section: Discussionmentioning
confidence: 46%
“…However, our mean dropout rate (25.2%) fell within the range of dropout rates in cognitive-behavioral therapy (e.g. 32% [19] and 15% [20,21]). …”
Section: Discussionmentioning
confidence: 46%
“…Several other studies have already reported PTSD symptom reduction after NET [28,29,30]; however, the positive impact of psychotherapy on a molecular parameter with potential long-term impact on physical health, i.e., DNA strand breakage, has not been demonstrated before. Although our sampling of tissue in the present study was restricted to PBMCs, we have presented a proof-of-principle for the reversibility of DNA strand breakage, an established risk factor in genomic instability and carcinogenesis, in somatic cells of individuals with PTSD after successful psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this procedure is to transform the generally fragmented reports of the implicitly coded traumatic experiences [27] into a coherent narrative, i.e., verbally accessible autobiographic memory. The efficacy of NET in improving PTSD symptomatology has been shown in a series of randomized controlled trials [28,29,30]. …”
mentioning
confidence: 99%
“…Narrative exposure therapy (NET) is an evidence-based treatment approach designed to treat survivors of organized violence who have endured multiple or continuous traumatic stressors and has proven effectiveness in torture survivors (Hensel-Dittmann et al, 2011;Neuner et al, 2010) (see Figure 4). NET addresses both the personal consequences and the political aspects of organized violence and torture.…”
Section: Figurementioning
confidence: 99%